A Complex Assembly Landscape for the 30S Ribosomal Subunit - Sykes, Michael T. (Annu Rev Biophys, 2009)
The ribosome is a complex macromolecular machine responsible for protein synthesis in the cell. It consists of two subunits, each of which contains both RNA and protein components. Ribosome assembly is subject to intricate regulatory control and is aided by a multitude of assembly factors in vivo, but can also be carried out in vitro. The details of the assembly process remain unknown even in the face of atomic structures of the entire ribosome and after more than three decades of research. Some of the earliest research on ribosome assembly produced the Nomura assembly map of the small subunit, revealing a hierarchy of protein binding dependencies for the 20 proteins involved and suggesting the possibility of a single intermediate. Recent work using a combination of RNA footprinting and pulse-chase quantitative mass spectrometry paints a picture of small subunit assembly as a dynamic and varied landscape, with sequential and hierarchical RNA folding and protein binding events finally converging on complete subunits. Proteins generally lock tightly into place in a 5′ to 3′ direction along the ribosomal RNA, stabilizing transient RNA conformations, while RNA folding and the early stages of protein binding are initiated from multiple locations along the length of the RNA.